Cor da pele e oposição à imigração: o papel do preconceito e das representações sociais sobre o Brasil - Costa Júnior, Clóvis Pereira da (2017)
This thesis aimed to investigate the role of prejudice and social representations about Brazil, here called "founding myths" in the relationship between skin color and opposition to immigration. It is assumed that this relationship is mediated by the myths and moderated by the level of prejudice of the participants. To achieve this goal, three articles were prepared. The first objective was to gather evidence of construct validity from the Scale of Fundamental Myths (SFM). By means of exploratory and confirmatory analyzes, the results showed that the measurement instrument has adequate statistical parameters in the solution with three factors. Article 2 aimed to investigate the mediating role of social representations about Brazil in the relationship between skin color and the opposition to immigration and to analyze these interactions from the moderating function of prejudice. The results pointed out the occurrence of mediation for the myths "racial democracy" and "respect for cultural diversity", respectively in the high and low levels of prejudice, indicating that the black immigrant suffers opposition from the activation of psychological mechanisms related to the denial of racial democracy and the perceived as a threat to the cultural balance of the country. In the third article, the justificatory discourses for the positioning of immigrants were analyzed, based on the immigrants' skin color. An excessive police approach to an immigrant was used as a setting for apprehending participants' justifications. The data were processed by the IRAMUTEQ software and revealed that, as a white immigrant, there were no positions favorable to police conduct. In relation to the black person, it was verified the occurrence of blame of this immigrant, including by means of adjectives, such as bandit and drug dealer. Taken together, the results obtained in this thesis demonstrate the importance of skin color as an organizing principle of the processes of social exclusion.